Politeness Strategies and Social Dimensions in Once Upon A Time Season 1 Movie Series: Sociopragmatics Study - HENDAR HENDAR; BUNGA GALUH ANDRETTA TRISNANDI (Universitas Widyatama, 2019)
The purposes of this research are to find out the types of politeness strategies used to save the face of the characters in Once Upon A Time season 1 and to identify the dominant scale of social dimensions when using politeness strategies in Once Upon A Time season 1. This research uses qualitative-descriptive analysis method and to get the data needed in this research the writer did the following steps: watching the movies, transcribing the speech, searching the data, classifying the data, analyzing the data and drawing a conclusion related to the types of politeness strategies and the dominant scale of social dimensions. The source of the data used is taken from the serial film Once Upon A Time season 1 by Edward Kitsis dan Adam Horowitz. The results of this research show that there are four types of politeness strategies found in the serial film Once Upon A Time season 1. They are 10 data of bald on-record (28,6%), 8 data of positive politeness strategies (22,9%), 13 data of negative politeness strategies (37,1%) and 4 data of off-record consists (11,4%) and the most dominant scale of four social dimension scales is social distance scale 14 data (40%).